A Review of Studies on action Songs among ESL Learners to Improve English - Kaur Swaran Singh, Charanjit; Jeganmohan, Sankeran (International Journal of Psychosocial Rehabilitation, 2020)
This paper reviews literature on using songs, particularly action songs, among ESL/EFL students. Several recent studies have found that action songs help the pupils to improve their English language skills. The use of action songs is hoped to help the pupils to enjoy learning during English lessons and to help them to be more focused and active in the lessons. Findings from the review revealed that songs, particularly action songs, can improve students’ English proficiency skills, motivation, and attitude with regard to the use of songs in the classroom and teachers’ and students’ perception of using songs. It shows that songs strengthen memory and recall, increase language skills, and promote social skills and cooperation.